INCREASING THE ECONOMIC EFFICIENCY OF INDUSTRIAL ENTERPRISES IN UZBEKISTAN - Saidova Mavludaxon Jumaboevna (Web of Journals Publishing, 2024)
This article discusses the key aspects that can contribute to increasing the economic efficiency of industrial enterprises in Uzbekistan. The main focus is on the introduction of new technologies and innovations, such as automation, robotics and digitalization of production processes. Measures to reduce energy consumption and improve energy efficiency are also discussed. Examples of successful implementation of technologies such as 3D printing and predictive analysis are given. The article analyzes the economic effect of these measures, including cost reduction and improved environmental sustainability.
Keywords: Economic efficiency, Industrial enterprises, Innovations, technology, automation, robotics, digitalization.